Effects of Oxidative Stress on Intestinal Type I Insulin-Like Growth Factor Receptor Expression - Baregamian, N.; Song, J.; Chung, D. H. (European Journal of Pediatric Surgery, 2012)
Introduction Oxidative stress activates multiple signaling transduction pathways, including the phosphatidylinositol 3-kinase (PI3-K), in an injured intestine as occurs in necrotizing enterocolitis (NEC). We have previously shown that hydrogen peroxide (H2O2)-induced PI3-K activation is significantly enhanced with exogenous insulin-like growth factor (IGF)-1 in intestinal epithelial cells. However, the effects of oxidative stress on IGF receptor type I (IGF-IR) activation and expression in the neonatal intestine during NEC are unknown.Material and Methods Intestinal sections from neonates undergoing bowel resections (control = 3, NEC = 20) were analyzed for IGF-IR expression. NEC was induced in newborn mouse pups using hypoxia and hyperosmolar feeds, and distal small bowel segments were analyzed for IGF-IR expression (control = 3, NEC = 7). H2O2 was used to induce oxidative stress in rat (RIE-1) and fetal human (FHs74 Int) intestinal epithelial cells. Phosphorylation of IGF-IR, Akt, a downstream effector of PI3-K, and IGF-IR levels were determined by Western blotting. Flow cytometry, immunofluorescence, immunohistochemistry, IGF-IR tyrosine phosphorylation array, cell death enzyme-linked immunosorbent assay, and Western blotting were used to determine the IGF-IR expression.Results An increased IGF-IR expression was noted in intestinal sections from NEC as well as murine model of NEC. H2O2 treatment rapidly activated IGF-IR and increased the expression in RIE-1 and FHs74 Int cells. Inhibition of IGF-IR resulted in significant RIE-1 cell apoptosis during oxidative stress. IGF-IR tyrosine phosphorylation array showed the recruitment of several key SH2 domain-containing proteins and oncogenes to the IGF-IR tyrosine kinase domain in H2O2-treated RIE-1 cells.Conclusion IGF-IR-mediated activation of intracellular signaling may play a critical role during oxidative stress-induced apoptosis in NEC.
Keywords: phosphatidylinositol 3-kinase/Akt; insulin-like growth factor type I receptor; oxidative stress; intestinal injury